The fishes of the groups Elasmobranchii, Holocephali, Isospondyli, and Ostarophysi[!] |b obtained by the United States Bureau of fisheries steamer "Albatross" in 1907 to 1910, chiefly in the Philippine islands and adjacent seas - Fowler, Henry Weed 1878-1965 (Smithsonian institution. United States National Museum. Bulletin 100, 1941)
contents: v.1 pt.1 The Philippine land shells of the genus Amphidromuspt.2 Ascidians from the Philippines and adjacent waters pt.3 Report upon the Scyphomedusae collected by the U.S. Bureau of Fisheries steamer "Albatross" in the Philippine islands and Malay archipelago. pt.4 Report on the Chaetognatha collected by the U.S. fisheries steamer "Albatross" during the Philippine expedition, 1907-1910. pt.5 Hydromedusae, Siphonophores and Ctenophores of the "Albatross" Philippine expedition